Brain derived neurotrophic factor in newly diagnosed diabetes and prediabetes. (5th July 2016) - Liu, Wei; Han, Xueyao; Zhou, Xianghai; Zhang, Simin; Cai, Xiaoling; Zhang, Lihua; Li, Yufeng; Li, Meng; Gong, Siqian; Ji, Linong
Abstract: Brain derived neurotrophic factor (BDNF) is thought to play an important role in glucose metabolism, but the exact mechanism has not been elucidated. The aim was to assess differences in serum BDNF levels across individuals with varying levels of glucose tolerance, and the association of serum BDNF levels with genetic variants and DNA methylation. Participants were selected from an ongoing population-based cohort study in rural China. In a randomly selected subsample of healthy participants (n = 33 males, n = 52 female), we assessed serum BDNF and in n = 50 of these, also DNA methylation. In a second subsample (all women; n = 28 with diabetes, n = 104 with prediabetes, and n = 105 age- and body mass index (BMI)-matched controls), we assessed serum BDNF and genetic variants. In a third subsample (all with diabetes; n = 7 normal BMI + low insulin level, n = 9 normal BMI + high insulin level, n = 9 obese + high insulin level), we assessed DNA methylation. Compared to age- and BMI-matched controls (24.71 (IQR, 20.44, 29.80) ng/ml), serum BDNF was higher in participants with prediabetes (27.38 (IQR, 20.64, 34.29) ng/ml), but lower in those with diabetes (23.40 (IQR, 18.12, 30.34) ng/ml) (P < 0.05). Two genetic variants near BDNF (rs4074134 and rs6265) were confirmed to be associated with BMI. BDNF CpG-6 methylation was positively associated with waist-to-hip ratio (P < 0.05). Furthermore, hyper-methylation in this site was found in participants with diabetes and high fasting insulin levels compared to those with diabetes and low fasting insulin levels, regardless of BMI status (P < 0.001 and P = 0.001, respectively). Observed differences in serum BDNF levels, genetic variants, and DNA methylation patterns across different glucose metabolic state suggest that BDNF may be involved in the pathophysiological process of insulin resistance and type 2 diabetes. Highlights: Serum BDNF was higher in prediabetes than normoglycemic controls. Serum BDNF was lower in those with diabetes than normoglycemic controls. BDNF CpG-6 methylation was positively associated with waist-to-hip ratio. Hyper-methylation in BDNF CpG-6 was in association with high fasting insulin levels.